Adaptive nulling through subarray switching in planar antenna arrays. Issue 3 (11th February 2016) - Salucci, M.; Poli, L.; Morabito, A.F.; Rocca, P.
Abstract : The suppression of undesired signals impinging on a planar antenna array from unknown directions is addressed by adaptively connecting and disconnecting subarrays of elements from the beamforming network. The subarrays, periodically arranged on the array aperture, are equipped with radio-frequency switches that are controlled to maximize the ratio between the power of the desired signal, whose direction of arrival is supposed to be known, and the total power received by the antenna. A set of numerical results concerning different subarray layouts and interfering configurations is reported and discussed to show the effectiveness of the nulling method and the behavior of the considered array architectures.